Institutional differences in USMLE Step 1 and 2 CK performance: Cross-sectional study of 89 US allopathic medical schools. - Jesse Burk-Rafel; Ricardo W Pulido; Yousef Elfanagely; Joseph C Kolars (PLoS ONE, 2019)
INTRODUCTION:The United States Medical Licensing Examination (USMLE) Step 1 and Step 2 Clinical Knowledge (CK) are important for trainee medical knowledge assessment and licensure, medical school program assessment, and residency program applicant screening. Little is known about how USMLE performance varies between institutions. This observational study attempts to identify institutions with above-predicted USMLE performance, which may indicate educational programs successful at promoting students' medical knowledge. METHODS:Self-reported institution-level data was tabulated from publicly available US News and World Report and Association of American Medical Colleges publications for 131 US allopathic medical schools from 2012-2014. Bivariate and multiple linear regression were performed. The primary outcome was institutional mean USMLE Step 1 and Step 2 CK scores outside a 95% prediction interval (≥2 standard deviations above or below predicted) based on multiple regression accounting for students' prior academic performance. RESULTS:Eighty-nine US medical schools (54 public, 35 private) reported complete USMLE scores over the three-year study period, representing over 39,000 examinees. Institutional mean grade point average (GPA) and Medical College Admission Test score (MCAT) achieved an adjusted R2 of 72% for Step 1 (standardized βMCAT 0.7, βGPA 0.2) and 41% for Step 2 CK (standardized βMCAT 0.5, βGPA 0.3) in multiple regression. Using this regression model, 5 institutions were identified with above-predicted institutional USMLE performance, while 3 institutions had below-predicted performance. CONCLUSIONS:This exploratory study identified several US allopathic medical schools with significant above- or below-predicted USMLE performance. Although limited by self-reported data, the findings raise questions about inter-institutional USMLE performance parity, and thus, educational parity. Additional work is needed to determine the etiology and robustness of the observed performance differences.